Investigação de conhecimentos de pais sobre o Trauma Craniano Violento e sua relação com o potencial de abuso infantil e o status socioeconômico - Soares, Ana Paula de Miranda Araújo (Universidade Federal de São Carlos, 2019)
This thesis is composed of three articles that aimed to investigate the risk factors involved in the occurrence of Abusive Head Trauma. The first one is a literature review whose purpose is to describe the risk factors associated with the family environment, characteristics of the child and the perpetrator. According to the review, the main risk factors described in the literature are socioeconomic vulnerability, stress situations, absence of support networks, inadequate prenatal care, children under three years of age, men with developmental deficit and male perpetrators. The need to investigate trauma-related knowledge, strategies used, abilities and beliefs of parents, as well as to enable health teams to detect the problem and to continuously deliver parent training programs are discussed. The second article consists of a qualitative analysis that aimed to present parents' knowledge regarding infant crying pattern and the consequences of shaking a baby, the strategies used to calm the crying baby, as well as managing the caregiver's stress at these times and maintaining their physical and emotional well-being. The results showed that less than half of the parents interviewed do not believe that shaking a baby can have moderate, serious or fatal consequences; almost all parents use strategies aimed at calming the crying baby, such as singing, talking to and holding him or her, although many strategies that could be effective are overlooked because of inadequate beliefs of these parents. In addition, most recognize that maintaining their physical and emotional well-being are important for them to be able to perform the tasks of nurturing their baby; however, few use strategies for stress management and frustration when the baby is crying. These topics are thus suggested to be addressed in prevention, intervention and parent training programs. Finally, the last article consists of a correlational analysis that sought to examine the relationship between parents' trauma-related knowledge, child abuse potential and socioeconomic status. Results show inadequate beliefs may be more present in lower socioeconomic classes, while the lack of knowledge about infant crying patterns is more common in higher socioeconomic classes. In addition, rigidity, that is, inflexibility concerning the child's behavior and appearance, seems to be related to inadequate beliefs about child care and also to lesser knowledge about the consequences of shaking a baby. It is therefore important that interventions are targeted to the needs of each target population and that a greater flexibility of parents' expectations for their children and themselves within their parenting role is emphasized.
Investigation of parents' knowledge on Abusive Head Trauma and its relation to their child abuse potential and socioeconomic status.
Keywords: Trauma Craniano Violento; Família; Abuso infantil; Abusive Head Trauma; Family; Child abuse; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA COGNITIVA